Появление концептa «Ёкaй» в японской культуре (Вестник КазНУ. Серия Востоковедения, 2017)
The article is dedicated to the concept of yokai, namely to its emergence in Japanese culture and further development. According to the author, the issue of supernatural beings in Japanese culture is of great importance in terms of both understanding mentality, psychology of Japanese people and studying the language and the history of this country.